2016
DOI: 10.1097/nnr.0000000000000137
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Among Chinese Patients With Rheumatoid Arthritis

Abstract: Patients with RA in mainland China experience impaired physical and mental health. Targeted and culturally sensitive interventions should be strengthened to improve the HRQoL of this population. Essentials in improving the HRQoL are enhancing self-efficacy, relieving fatigue, delaying the onset of disabilities, increasing social support, and controlling disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 3 publications
11
35
0
Order By: Relevance
“…The higher the total score, the higher the degree of fatigue is. The Chinese version of MFI has been applied to patients with high reliability and validity [8, 38]. The Cronbach ’s α value of the MFI was 0.91 in the current study.…”
Section: Methodsmentioning
confidence: 82%
See 4 more Smart Citations
“…The higher the total score, the higher the degree of fatigue is. The Chinese version of MFI has been applied to patients with high reliability and validity [8, 38]. The Cronbach ’s α value of the MFI was 0.91 in the current study.…”
Section: Methodsmentioning
confidence: 82%
“…Compared with the US and Egypt, RA patients in the UK and the Netherlands seemed to be dealing with their fatigue by themselves without seeking help from others, thus suffering from greater severity of symptoms [5, 5759]. A Chinese study reported that social support, as a direct or indirect factor, played an important predicting role in health-related quality of life both physically and psychologically[8]. But some researches have reported that patients with RA always lack adequate social support [15, 16], probably because RA is incurable with a prolonged course, causing even deformity and physical disability in the final stage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations